2018
DOI: 10.1097/md.0000000000012772
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of desflurane and total intravenous anesthesia on the optic nerve sheath diameter in robot assisted laparoscopic radical prostatectomy

Abstract: Background:Optic nerve sheath diameter (ONSD) is a well-known surrogate marker for intracranial pressure during robot-assisted laparoscopic radical prostatectomies (RALP). ONSD during RALP is known to increase due to elevated intracranial pressure as a result of the steep Trendelenburg position and carbon dioxide pneumoperitoneum. We aimed to compare the effects of total intravenous anesthesia (TIVA) and desflurane anesthesia (DES) on ONSD during RALP.Methods:Patients scheduled for RALP were enrolled and rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 19 publications
2
15
1
6
Order By: Relevance
“…Contrary to our findings, Yu et al [ 24 ] and Choi et al [ 25 ] showed that the ONSD was significantly lower during propofol anesthesia than during inhalation anesthesia after CO 2 pneumoperitoneum induction and Trendelenburg positioning in RALRP. Yu et al [ 24 ] reported that there are no significant differences in the ONSD between the two groups until 30 min after CO 2 pneumoperitoneum induction and Trendelenburg positioning, corresponding to T3 of our study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our findings, Yu et al [ 24 ] and Choi et al [ 25 ] showed that the ONSD was significantly lower during propofol anesthesia than during inhalation anesthesia after CO 2 pneumoperitoneum induction and Trendelenburg positioning in RALRP. Yu et al [ 24 ] reported that there are no significant differences in the ONSD between the two groups until 30 min after CO 2 pneumoperitoneum induction and Trendelenburg positioning, corresponding to T3 of our study.…”
Section: Discussioncontrasting
confidence: 99%
“…These two factors, anesthesia time and average age of patients, may be the cause of the differences in the results when compared with those of our study. Choi et al [ 25 ] also reported that the mean ONSD in a propofolbased TIVA group is significantly lower than in a desflurane group in RALRP. They showed that the effect of inhalation anesthetics on increasing cerebral blood flow is dependent on the intrinsic cerebral vasodilatory activity and cerebral vascular smooth muscle relaxation in a dose-dependent manner [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides dexmedetomidine, a few studies evaluated the effects of different anesthetic methods used during RALP on ONSDs. [15,33] In a previous study, propofol anesthesia during RALP significantly decreased ONSD after pneumoperitoneum and steep Trendelenburg position, compared to that of sevoflurane anesthesia, suggesting that propofol might help minimize ICP changes in robotic prostatectomy patients [15] . In another study, the effects of desflurane and total intravenous anesthesia with propofol and remifentanil during RALP on ONSD were compared.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the effects of desflurane and total intravenous anesthesia with propofol and remifentanil during RALP on ONSD were compared. Total intravenous anesthesia with propofol and remifentanil was shown to be a more suitable anesthetic option for patients undergoing RALP [33] . Therefore, dexmedetomidine or propofol administration could help minimize the increase in ICP during RALP.…”
Section: Discussionmentioning
confidence: 99%
“…Çalışmalar göstermiştir ki ultrasonografi eşliğinde optik sinir kılıf çapı ölçümü artmış kafa içi basıncı için noninvaziv ve üretilebilir bir tekniktir (14). Robot yardımlı laparoskopik radikal prostatektomilerde desfluran ve total intravenöz anestezinin optik sinir kılıf çapına etkilerinin karşılaştırıldığı randomize kontrollü bir çalışmada ortalama optik sinir kılıf çapının propofol-remifentanil grubunda desfluran-remifentanil grubuna göre anlamlı olarak daha düşük olduğu bulunmuştur (15). Bu çalışmada total intravenöz anestezinin serebral hipoperfüzyon için risk taşıyan veya intrakraniyal basıncı yüksek hastalarda daha uygun bir seçim olabileceği belirtilmiştir.…”
Section: Bulgularunclassified